2012
DOI: 10.1007/s10165-012-0634-9
|View full text |Cite
|
Sign up to set email alerts
|

Mycophenolate mofetil versus intravenous cyclophosphamide for induction treatment of proliferative lupus nephritis in a Japanese population: a retrospective study

Abstract: MMF may be used as an alternative to IVC for inducing renal remission of LN in Japanese patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…A total of 70 unique publications (3,4,10,11, comprised of 27 clinical studies, 16 epidemiologic studies, and 27 studies reporting economic and humanistic burden and unmet need met the inclusion criteria (see Supplementary Appendix C, available at http:// onlinelibrary.wiley.com/doi/10.1002/acr.24431/abstract). Most of the studies were conducted in China (n = 14) (11,19,21,23,28,29,38,43,47,54,59,78,79,82), Japan (n = 13) (31,(33)(34)(35)(36)(37)40,58,65,67,74,75,77), and Taiwan (n = 12) (20,22,24,25,45,52,56,60-62, 64,69), followed by Korea (n = 9) (17,26,32,42,44,53,63,72,76), Australia (n = 7) (4,18,39,49,50,57,…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A total of 70 unique publications (3,4,10,11, comprised of 27 clinical studies, 16 epidemiologic studies, and 27 studies reporting economic and humanistic burden and unmet need met the inclusion criteria (see Supplementary Appendix C, available at http:// onlinelibrary.wiley.com/doi/10.1002/acr.24431/abstract). Most of the studies were conducted in China (n = 14) (11,19,21,23,28,29,38,43,47,54,59,78,79,82), Japan (n = 13) (31,(33)(34)(35)(36)(37)40,58,65,67,74,75,77), and Taiwan (n = 12) (20,22,24,25,45,52,56,60-62, 64,69), followed by Korea (n = 9) (17,26,32,42,44,53,63,72,76), Australia (n = 7) (4,18,39,49,50,57,…”
Section: Resultsmentioning
confidence: 99%
“…Disease characteristics of patients in included studies. Disease characteristics were reported for SLE patients in studies from Australia (n = 6) (4,18,39,50,57,66), China (n = 15) (11,19,21,23,28,29,38,43,47,54,59,78,79,82), Hong Kong (n = 6) (10,30,46,71,80,81), Japan (n = 13) (31,(33)(34)(35)(36)(37)40,58,65,67,74,75,77), Korea (n = 7) (17,26,41,42,44,63,72), Singapore (n = 4) (27,48,55,70), and Taiwan (n = 10) (20,22,24,25,45,52,…”
Section: Significance and Innovationsmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, El-Shafey et al's data suggest MMF as an alternative treatment to induction by pulse cyclophosphamide [24]. However, Onishi et al deferred the MMF superiority to pulse cyclophosphamide induction [25]. Kallenberg demonstrated that both the Euro-Lupus protocol and MMF with corticosteroids might be considered for remission induction in patients with proliferative LN [26].…”
Section: Discussionmentioning
confidence: 99%